Utilizing X-ray radiography for non-destructive assessment of paddy rice grain quality traits - Tharanya, M.; Chakraborty, D.; Pandravada, A.; Babu, R.; Gangashetti, M.; Paidi, S.; Choudhary, S.; Sivasakthi, K.; Anbazhagan, Krithika; Vaditandra, B.; Waininger, M.; Weule, M.; et al. (BioMed Central, 2025)
Background: Agricultural systems are under extreme pressure to meet the global food demand, hence necessitating faster crop improvement. Rapid evaluation of the crops using novel imaging technologies coupled with robust image analysis could accelerate crops research and improvement. This proof-of-concept study investigated the feasibility of using X-ray imaging for non-destructive evaluation of rice grain traits. By analyzing 2D X-ray images of paddy grains, we aimed to approximate their key physical Traits (T) important for rice production and breeding: (1) T1 chaffiness, (2) T2 chalky rice kernel percentage (CRK%), and (3) T3 head rice recovery percentage (HRR%). In the future, the integration of X-ray imaging and data analysis into the rice research and breeding process could accelerate the improvement of global agricultural productivity.